Analisis Karakteristik dan Tingkat Pencemaran Air Limbah Industri Tahu Serta Uji Toksisitas LC50 Terhadap Ikan Nila (Oreochromis Niloticus) di Kabupaten Karawang - Izzatul Muslimah, Nazhifa; Rendy Rifki Ramadhan; Zaina Nandini Maulid; Azka Rahmat Mujadi; Haratul Roby Al Mukaromah; Naufal Zahran Qaniurizqi (Jurnal Serambi Engineering, 2026)
This study was conducted to identify the characteristics of liquid waste produced by the tofu industry and to assess its toxicity level to tilapia (Oreochromis niloticus). The study used a completely randomised design (CRD) with five variations in waste concentration, namely 0%, 3%, 6%, 9%, and 12%, each with three replicates, resulting in a total of 150 test fish. The parameters observed included fish mortality, temperature, pH, and test media conditions during observation. The results showed that the water temperature was relatively stable in the range of 26.5–28.7°C, while the pH value fluctuated between 4.36 and 9.66 as the waste concentration increased. The percentage of fish mortality increased from 0% in the control treatment to 73% at the highest concentration. Based on the probit analysis results, an LC₅₀ value of 9.4% was obtained, indicating that tofu wastewater has a fairly high level of toxicity and has the potential to pollute the aquatic environment if it is not treated before disposal.